The Neuropsychological Basis of Discourse Comprehension (Linguist, 2025)
This paper examines the role of the neuropsychological mechanisms involved in high-level cognitive processes of understanding and cohesion of discourse. The FMRI has contributed to the discovery of these foundations depending on the cases of injured patients, especially those with right-brain damage. Among the general knowledge mechanisms, we recall the critical role of attention, memory, procedural processes, and interpretation of literal meaning inside the left brain.The understanding of discourse was also treated in relation to a wide range of psychological factors (among these, psychological intelligence and personality traits). It was assumed that the right brain bears some semantic operations, such as the ability to generate inferences, to link between operations in the nervous system, and the treatment of concepts as well as their association.However, the most important results show that subjects with right-brain injury have an inability to integrate semantic information to construct a coherent representation of discourse, a failure to understand jokes and humor, as well as metaphors, a low capacity to generate representations of the mental situation, an inability to link between pronunciation and context, and difficulties in understanding idioms and indirect questions. This indicates that the right brain is sensitive to the emotional level of non-verbal written or spoken discourse.Despite the foregoing, the role of the right brain in processing, linguistic comprehension, and discourse analysis remains secondary compared to the left brain. Finally, the neuropsychological literature could not identify one specific area in the brain that includes cognitive processes during the understanding of discourse.
Keywords: Understanding; discourse; right brain; cognitive processes; inference; semantic integration; temporal parietal areas; mental representations